Justification-Suppression and Normative Window of Prejudice as Determinants of Bias Toward Lesbians, Gays, and Bisexual Adoption Applicants. Issue 4 (21st March 2019) - DeVault, Alicia; Miller, Monica K.
ABSTRACT: Despite gains in equality for lesbians, gays, and bisexuals (LGB), these couples still face discrimination in adoption scenarios. Guided by the normative window of prejudice and the justification-suppression model, participants read about a suitable or unsuitable couple applying to adopt a child. Participants indicated whether the couple should be allowed to adopt the child and how committed the couple is to being parents. Heterosexuals were perceived as less committed parents compared to LGB parents; sexual orientation was not related to adoption decisions. There was a significant interaction between sexual orientation and suitability for perceptions of commitment to parenting: in the suitable condition, heterosexuals were perceived as less committed parents compared to gays; in the unsuitable condition, heterosexuals were perceived as less committed parents compared to bisexuals. This interaction was nonsignificant for adoption decisions. Future research should determine if these findings relate to other sexual orientations or gender identities.